1968
DOI: 10.1021/ja01008a026
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of the photochemical rearrangement of lumisantonin

Abstract: For PhzCO + hv + In conversions in excess of 50%, the reaction mixture at the end of the dark reaction will contain In, which will ultimately have to react with atmospheric oxygen upon admission of air. one can easily obtain quantum Yields of Ph2CO disappearance ranging from 1 to 2. The only case in which this quantum yield can be close to 2 is if the Abstract: Sensitization studies on the photolysis of lumisantonin together with a reinvestigation of its pyrolysis have yielded results which support a mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1969
1969
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…It has been suggested that oxyallyl compounds are intermediates in both thermal and photochemical rearrangements of bicyclo[3.1.0]hex-3-en-2-ones to phenols [25][26][27][28][29][30][31][32][33][34][35]. Some time ago, we studied the reaction pathway for the prototype rearrangement of bicyclo[3.1.0] hex-3-en-2-one (1a) to phenol (3a) in the gas phase at the CASSCF/CASPT2 level [36].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that oxyallyl compounds are intermediates in both thermal and photochemical rearrangements of bicyclo[3.1.0]hex-3-en-2-ones to phenols [25][26][27][28][29][30][31][32][33][34][35]. Some time ago, we studied the reaction pathway for the prototype rearrangement of bicyclo[3.1.0] hex-3-en-2-one (1a) to phenol (3a) in the gas phase at the CASSCF/CASPT2 level [36].…”
Section: Introductionmentioning
confidence: 99%
“…The substituent effect of a methyl group at C-2 and C-4 was also studied in the octalone system (16,17). Dienone 38 which has a C-2 methyl gave a bicyclic enone (39)…”
Section: Hir ^ 38mentioning
confidence: 99%
“…The spectroscopic investigation of six steroidal ketones (5)(6)(7)(8)(9)(10) by phosphorescence excitation and emission methods was carried out by Keams and coworkers in 1968 (3, 4). Direct absorption and phosphorescence excitation 3 * techniques allowed location of the (n,TT ) states.…”
Section: Spectroscopic Studies Of 2-cyclohexenonesmentioning
confidence: 99%
“…Fisch and Richards(8) have investigated the triplet state of lumissntonin (3^) by phosphorescence techniques. The molecule exhibits a weak structureless emission with the 0-0 band at 64-+ kcal/mole.…”
mentioning
confidence: 99%